Vesico -Uterine Fistula - Bedoya Hevia, Mariano (1965)
I have considered of great interest to present the first case of vesico - uterine fistula ( L vu ), followed by cesarean section , observed in the Hospital Loayza , Pavilion 5, Room 2nd descriptions in the literature are not very numerous. Neugeveaur in 1888 (quoted by Knipe 1908 ) (3 ) , in a review of cases of urogenital fistulas, found a case that opened near the internal os of the cervix . Mac Kenzie (1921 ) (quoted by Myron Nourse ) (7 ) observed a case. Kirchner ( 1933 ) cit. by Magri ( 3) published a new observation . Laffont and Ezes ( 5) ( 1946 ) reviewed the subject in a publication that they titled , " utero- vesical fistula with a single direction and rules " , consecutive cesarean section . Mazingarbe and Musset (quoted by Moonen ) (4 ) makes references to two new observations followed caesarean section. Bond and Rogers ( 1) ( 1952 ) , work in a well-documented report a case after a laparotraquelotomía . Myron Nourse and W. IEES N ( 7) ( 1954 ) , reported a case of f . v . u. presenting with fetal parts by the external urethral meatus. Yngelman - Sumberg (quoted by Musset ) (5 ) , a case study whose etiology vaginal cesarean. Moonen (4 ) ( 1955 ) . an interesting report adds a new case after cesarean . Youssef (1957 ) reports a case. Falk and Tancer , Gilbert, of Bloode of Stening (1956) and Youssef (1959 ) (quoted by Musset and others) (5), extensively reviewed the subject. MM Gorsse Ostovar and ( 9) ( 1959) , have studied a consecutive case introduced above shoulder cesareado a uterus , practiced embryotomy .